Selective disruption of gray matter volume covariance in orbitofrontal cortex subregions among patients with functional constipation - Qian Su; Lianzi Liu; Ting Hua; Jian Gong; Hongliang Tian; Jiongyue Yun; Wangli Cai (Scientific Reports)
Abstract Functional constipation (FCon) is a prevalent common functional gastrointestinal disorders (FGIDs) frequently linked to mental and psychological disorders. Although previous studies have demonstrated alterations in brain structure and function in FCon, there remains a lack of investigation into the network-level structural inter-relationships (e.g., structural covariance) within key regions such as the orbitofrontal cortex (OFC). This study aimed to investigate whether gray matter volume (GMV) covariance in OFC subregions is selectively disrupted in FCon patients. A cohort of 87 patients with FCon and 87 healthy controls (HC) underwent high-resolution structural MRI scans. The GMV covariance was analyzed using voxel-based morphometry, and the covariance patterns between OFC subregions and other brain regions were examined using a general linear model. FCon patients demonstrated selective alterations in GMV covariance, notably within the lateral and medial OFC subregions, which showed altered covariance with brain regions associated with sensory, motor, and cognitive control functions, including the olfactory cortex, supplementary motor area, insula, and superior frontal gyrus. Our findings indicate that FCon patients show specific GMV covariance alterations in the OFC subregions, suggesting that these structural changes may be associated with disrupted brain–gut interactions and gastrointestinal dysfunction in patients with functional constipation, though the complex and bidirectional nature of gut–brain communication warrants further investigation.